2018
DOI: 10.1002/1873-3468.13260
|View full text |Cite
|
Sign up to set email alerts
|

SOX‐11 regulates LINE‐1 retrotransposon activity during neuronal differentiation

Abstract: Activity of the human long interspersed nuclear elements‐1 (LINE‐1) retrotransposon occurs mainly in early embryonic development and during hippocampal neurogenesis. SOX‐11, a transcription factor relevant to neuronal development, has unknown functions in the control of LINE‐1 retrotransposon activity during neuronal differentiation. To study the dependence of LINE‐1 activity on SOX‐11 during neuronal differentiation, we induced differentiation of human SH‐SY5Y neuroblastoma cells and adult adipose mesenchymal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
(65 reference statements)
0
5
0
Order By: Relevance
“…Two binding sites for SRY factors have been mapped in the human L1 promoter region, and both are required for the activation of an L1 reporter system in human rhabdomyosarcoma (RD) cells (Tchénio et al 2000). SOX11 was specifically shown to transactivate a reporter gene in RD cells, which has been further supported in a recent study demonstrating the direct role of SOX11 in activating L1Hs during SH-SY5Y cells neuronal differentiation (Orqueda et al 2018). SOX2 was shown to repress L1Hs transcription in neural stem cells.…”
Section: Dynamic Evolution Of Te Regulatory Regionsmentioning
confidence: 83%
“…Two binding sites for SRY factors have been mapped in the human L1 promoter region, and both are required for the activation of an L1 reporter system in human rhabdomyosarcoma (RD) cells (Tchénio et al 2000). SOX11 was specifically shown to transactivate a reporter gene in RD cells, which has been further supported in a recent study demonstrating the direct role of SOX11 in activating L1Hs during SH-SY5Y cells neuronal differentiation (Orqueda et al 2018). SOX2 was shown to repress L1Hs transcription in neural stem cells.…”
Section: Dynamic Evolution Of Te Regulatory Regionsmentioning
confidence: 83%
“…The L1 promoter region also contains two SRY-binding sites for the SOX transcription factor family [388], expressed in embryonic tissues, testes, and in various tissues in the adult body with the highest expression level in the brain, especially for the SOX2 factor [244]. SOX11 regulates L1 during the differentiation of neuronal tissues [388,389]. SOX2 enhances L1 expression in hippocampal neuronal stem cells in the adult brain [113,390].…”
Section: Positive Regulation Of L1mentioning
confidence: 99%
“…Consistently, we showed that GATA2 was downregulated in high-risk NB. Consistently, ID1, SOX11, TFAP2B, KLF7, and GATA3 were linked to neurogenesis or NB differentiation [ 13 , 18 , 19 , 23 , 71 , 72 ], but to our knowledge, these studies did not discuss their association with survival and risk groups in NB, hence our findings are novel.…”
Section: Discussionmentioning
confidence: 57%